Reduced Population Burden of Road Transport–related Major Trauma After Introduction of an Inclusive Trauma System. Issue 3 (March 2015) - Gabbe, Belinda J.; Lyons, Ronan A.; Fitzgerald, Mark C.; Judson, Rodney; Richardson, Jeffrey; Cameron, Peter A.
Abstract : Objective: To describe the burden of road transport–related serious injury in Victoria, Australia, over a 10-year period, after the introduction of an integrated trauma system. Background: Road traffic injury is a leading cause of death and disability worldwide. Efforts to improve care of the injured are important for reducing burden, but the impact of trauma care systems on burden and cost of road traffic injury has not been evaluated. Methods: All road transport–related deaths and major trauma (injury severity score >12) cases were extracted from population-based coroner and trauma registry data sets for July 2001 to June 2011. Modeling was used to assess changes in population incidence rates and odds of in-hospital mortality. Disability-adjusted life years, combining years of life lost and years lived with disability, were calculated. Cost of health loss was calculated from estimates of the value of a disability-adjusted life year. Results: Incidence of road transport–related deaths decreased (incidence rate ratio 0.95, 95% confidence interval: 0.94–0.96), whereas the incidence of hospitalized major trauma increased (incidence rate ratio 1.03, 95% confidence interval: 1.02–1.04). Years of life lost decreased by 43%, and years lived with disability increased by 32%, with an overall 28% reduction in disability-adjusted life years over the decade. There was a cost saving per case of A$633, 446 in 2010–2011 compared with the 2001–2002 financial year. Conclusions: Since introduction of the trauma system in Victoria, Australia, the burden of road transport–related serious injury has decreased. Hospitalized major trauma cases increased, whereas disability burden per case declined. Increased survival does not necessarily result in an overall increase in nonfatal injury burden. Abstract : This population-based study found that since the introduction of an inclusive, regionalized trauma system in Victoria, Australia, the burden of road transport–related serious injury has decreased. Hospitalized major trauma cases increased, but disability burden per case declined. Increased survival did not result in an overall increase in nonfatal injury burden.